Legal Education for The Future of Indonesia: a Critical Assessment - Irianto, Sulistyowati (The Indonesian Journal of Socio-Legal Studies, 2021)
This paper aims to analyze the extent to which higher education in law is able to prepare graduates to think critically and respond in a reform-minded way to changes in society. Legal developments have always been unable to catch up with the speed of change in society, especially due to political constraints in the law-making process. This paper aims to explain the position of legal education which attempts to bridge the gap between the law-making process, the existing normative legal system, and community development. To what extent are legal education managers open to formulating and implementing the curriculum? Is there enough space to enrich the legal science with a new approach and methodology, in order to analyze the development of legal practice more fundamentally? To what extent does interdisciplinary law studies have a place in the curriculum? The answer to these questions will have an impact on the development of legal science and the future of law enforcement in Indonesia.